An initial consideration of data availability issues in downscaling ocean accounting to inform sustainable aquaculture development: The example of Clew Bay, Ireland. (November 2022) - McManus, Catherine; McIlgorm, Alistair; Nichols, Rachel; Cooper, Andrew
Abstract: With the international prioritisation of sustainable development for management of marine resources and areas, those involved in marine industry are seeking how they progress their environmental, economic and social relationships, in a sustainable manner. Ocean accounting is an emerging tool that may enable stakeholders to integrate data and information from different disciplinary areas, bringing it together to facilitate sustainable development. The case of Clew Bay, Ireland is examined to see the extent to which ocean accounts may be translated to a regional marine area. The study identifies significant gaps between nationally available marine data sets and the regional requirements of ocean accounts. These reflect past marine governance, management and policy approaches and suggests that progressing ocean accounts in regional areas will require significant realignment and adaptation by agencies providing marine data to meet the needs of stakeholder groups such as aquaculturists. The case study indicates that pilot exercises based around ocean account information are required for government agencies and stakeholders to develop more integrated plans for a sustainable industry and regional community. Highlights: Government and industry are seeking ocean governance and management tools to achieve sustainable development. Internationally ocean accounting is a developing process that includes economic and environmental values in policy decision making. Information on the national ocean economy has been an important start in providing data for marine management. The study finds that construction of ocean accounts for Clew Bay, Ireland was limited by insufficient or inappropriate data available for key ecosystem and economic indicators; common problems were a lack of fine-scale, time series data for the region. More work is needed in exploring the suitability of ocean accounts for localised areas, with collaboration between regional stakeholders, data collection agencies and national-level sustainability frameworks likely needed to facilitate ocean accounting efforts into the future.